Fashion Shopping from a VNA Perspective: Telling the Untold Story - Lee, Galn; Woodside, Arch; Zhang, Mann (Korean Academy of Marketing Science, 2013)
This study explores the fashion shopper’s conscious and unconscious motivations and feelings by replicating and extending the virtual narrative art (VNA) research design of Woodside and Megehee. Based on the evidences from the blog and the movie, in visual forms such as text excerpts and pictures, this study creates two accounts of VNA that link the fashion shopping experience in a series of contextual narratives. The study sheds new light on fashion shopper’s shopping motivations and experience.